2012
DOI: 10.1017/s1355617712000872
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Clinical Course, and Predictors of Prolonged Recovery Time Following Sport-Related Concussion in High School and College Athletes

Abstract: Sport-related concussion (SRC) is typically followed by clinical recovery within days, but reports of prolonged symptoms are common. We investigated the incidence of prolonged recovery in a large cohort (n = 18,531) of athlete seasons over a 10-year period. A total of 570 athletes with concussion (3.1%) and 166 controls who underwent pre-injury baseline assessments of symptoms, neurocognitive functioning and balance were re-assessed immediately, 3 hr, and 1, 2, 3, 5, 7, and 45 or 90 days after concussion. Conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
272
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(288 citation statements)
references
References 33 publications
11
272
4
1
Order By: Relevance
“…These results are in agreement with other studies that have demonstrated alterations in accommodation, convergence, and saccades following concussion 22,30,31 and 1 study that found that abnormal convergence was associated with prolonged recovery following pediatric concussion. 8 Previous studies have also suggested that a preinjury mood disorder 8,29 and posttraumatic amnesia 23 are independent predictors of longer recovery following SRC.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with other studies that have demonstrated alterations in accommodation, convergence, and saccades following concussion 22,30,31 and 1 study that found that abnormal convergence was associated with prolonged recovery following pediatric concussion. 8 Previous studies have also suggested that a preinjury mood disorder 8,29 and posttraumatic amnesia 23 are independent predictors of longer recovery following SRC.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms from most concussions resolve in <2 weeks [8]; however, for some athletes the symptoms can persist for longer than 1 month [9]. In that intervening period, athletes may experience a combination of cognitive, somatic and emotional symptoms [9,10] that can impair their ability to complete school or work obligations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates as to duration of postconcussive symptoms in children range widely, with reports showing as few as 10% of patients symptomatic 7 days after sport-related concussion 4 to as many as 43% still with symptoms 3 months after being hospitalized for mTBI. 5 One cohort study conducted in the emergency department (ED) setting showed 29.3% of children aged 5 to 18 years still symptomatic 3 months after sustaining a concussion, with the most common symptoms being headache, fatigue, and frustration.…”
mentioning
confidence: 99%